Os grupos dos onze no Paraná: trajetórias - Pradela, Luana Milani (2019)
The Eleven Companions’ Group or Nationalist Commands, were organized in the pre-blow military period of 1964, in Brazil, all regions are based on the speeches of the labor politician Leonel Brizola, who "claimed" for popular support in a context of social and economic tension that lived the country. However, little things were explored about these groups’ organization in the state of Paraná. Who were these guys? What were you defending? Have they suffered reprisals on the part of dictatorial organization´s repression? The documents produced and seized by the Department of Political and Social order of Paraná, present in the state public archives, will allow us, based on a critical analysis, to better understand the organization and intent of these people who were linked to Eleven Companions’ Group summoned by Brizola, in a advancing nationalist context discourses and the possibility of applying the basic reforms proposed by the João Goulart government, in particular defense of agrarian reform, which emerged as an alternative to precarious living conditions in the countryside.